A thorough examination of the causes, diagnosis, and treatment of erectile dysfunction: A comprehensive review - Farhat, Muhammad Fauzan (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Erectile dysfunction (ED) is a complex sexual disorder and a significant clinical indicator of vascular, metabolic, endocrine, neurological, psychological, and relational health. This brief narrative review encapsulates the prevailing evidence regarding the etiology, diagnosis, and treatment of erectile dysfunction (ED). Methods: From 2016 to 2026, we gave priority to peer-reviewed guidelines, consensus statements, systematic reviews, meta-analyses, and high-impact reviews. Results: The evaluation of ED should incorporate a sexual and medical history, a validated symptom assessment, a focused examination, selective laboratory testing, and cardiovascular risk assessment. The primary treatment continues to focus on lifestyle enhancement and phosphodiesterase type 5 inhibitors. Conversely, vacuum devices, localized vasoactive therapy, testosterone for verified hypogonadism, psychosexual treatment, and penile prostheses are employed based on patient phenotype and preference. Low-intensity shockwave therapy may be advantageous in specific instances of vasculogenic disease, whereas platelet-rich plasma and stem cell methodologies remain subject to ongoing research. Conclusion: Emergency management should be systematic, evidence-based, and focused on the patient, with prompt identification of systemic disease and the exclusion of unverified treatments.